Antibiotic Resistance: What are the Opportunities for Primary Care in Alleviating the Crisis? - Hansen, Malene Plejdrup; Hoffmann, Tammy C.; McCullough, Amanda R.; van Driel, Mieke L.; Del Mar, Chris B. (Frontiers in Public Health, 2015)
• Preventing patients from developing an acute respiratory infection will obviate any need for antibiotic use downstream. Hygiene measures (such as physical barriers and hand hygiene), and possibly vaccination and exercise, may be effective for preventing some acute respiratory infections. • Patients overestimate the effectiveness of antibiotics: therefore public campaigns might contribute to minimise misconceptions. • Complementary and alternative medicines (e.g. zinc, caffeine, vitamin C, probiotics and Echinacea) are often proposed for preventing and treating acute respiratory infections, but evidence for efficacy is scarce. • General practitioners’ attitudes towards antibiotic prescribing are a major factor in the prescribing for acute respiratory infections. Professional interventions with educational components are effective, although they have modest effects, and are expensive. • General practitioners’ perceptions – that mistakenly assume as a default that patients want antibiotics for their acute respiratory infections – are often wrong. Shared decision making might be a solution, as it enables clinician and patient to participate jointly in making a health decision, having discussed the options together with the evidence for their harms as well as benefits. • General practitioners’ diagnostic uncertainty – often leading to an antibiotic prescription ‘just in case’ – might be addressed by exploiting strategies such as safety-netting, e.g. establishing with the patient a priori clearly defined actions to take if the course of the illness deviates from the expected. However, there is scant research undertaken in this area and evaluation of this strategy and its effects on patient care is needed. • The best strategies for the future are likely to focus on the best combination of the most effective interventions rather than any single one.